Controlling System for Cloud and Sensor Networks by Authenticated Trust and Reputation Calculation Integration - M, Ms.Vedambika; Rani S, Ms. Soja (IJRDO -Journal of Computer Science Engineering, 2016)
he integration Cloud computing – Wireless sensor network has been attracting the attention of several researchers both in the academia and the industry as it provides many opportunities for organizations by offering a range of computing services. So, data gathering capability of wireless sensor networks (WSNs) become easy. For cloud computing to become widely adopted by both the enterprises and individuals, several issues have to be solved. In any case, authentication as well as trust and reputation calculation and management of cloud service providers (CSPs) and sensor network suppliers (SNPs) are two exceptionally critical and barely explored issues for this new paradigm. To fill the gap, our paper proposes a novel authenticated trust and reputation calculation and management (ATRCM) framework for CC-WSN combination or integration. Considering the authenticity of CSP and SNP, the attribute necessity of cloud service user (CSU) and CSP, the expense, trust, and reputation of the service of CSP and SNP, the proposed ATRCM framework accomplishes the three functions: 1) verifying CSP and SNP to stay away from malicious impersonation attacks; 2) computing and managing trust and reputation with respect to the service of CSP and SNP; and 3) helping CSU choose desirable CSP and assisting CSP in selecting suitable SNP. Detailed analysis and design as well as further functionality evaluation result are presented to exhibit the effectiveness of ATRCM, followed with system security analysis